Inhibition of Herpesvirus hominis replication by human interferon. - Rasmussen, L (1975)
The effect of human interferon on single-cycle replication of Herpesvirus hominis type 1 (HV-1) and vesicular stomatitis virus (VSV) in human foreskin fibroblast cultures (HFF) was studied. After treatment of HFF cultures with low concentrations (58 U) of human interferon, a variable but statistically significant inhibition of HV-1 was observed. At higher concentrations (greater than 95 U) yield reduction of HV in interferon-treated cultures approached that of VSV. Preliminary data indicate that antiviral activity decays more rapidly for HV-1 than for VSV after removal of interferon from cultures.